Gaining comprehensive data about sexual knowledge through surveys - Zahra Karimian; Effat Merghati Khoei; Raziyeh Maasoumi; Marzieh Araban; Mahboobeh Rasoulzadeh Bidgoli; Shahrokh Aghayan; Seied Ali Azin (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Delivery of sexual health services rely on rigorous facts extracted from surveys, but often those facts cannot be available due to the lack of culturallysensitive questionnaires. Objective: our aim was to show the validity and reliability of the Persian version of the Acquisition of Sexual Information Test (ASIT), a measure selected due to its assemblages with Iranian culture. Materials and Methods: Forward-backward procedure was applied to translate the questionnaire. Cross-sectional study was carried out and psychometric properties of the Iranian version were tested in a thirty sample of reproductive-age women. Face validity was assessed by qualitative and quantitative methods. Content validity was also assessed by calculating two quantitative indicators as content validity index (CVI) and content validity ratio (CVR). Reliability was assessed by test-retest analyses. Results: Impact score was 1.5, the majority of participants (83.3%) stated that the overall level of questionnaire was high but some of the questions were irrelevant to sexual knowledge. Many questions (90%) gained a CVR less than 0.56, and all of them gained CVIs lower than 0.7. Correlation in test-retest reliability was 0.85. Conclusion: sexual knowledge questionnaire seems to be culturally inappropriate for Iranian women. Although, we need survey data for assessing the evidence-based needs for sexual health and best practice, but the questions addressing various dimensions of sexuality must be culturally sensitive, comprehensive and appropriate. Our findings suggest that ASIT as a well-known measure should be used in Iranian population with caution.